On the Zeros of the Big q-Bessel Functions and Applications - Fethi Bouzeffour; Hanene Ben Mansour; Mubariz Garayev (Mathematics, 2020)
This paper deals with the study of the zeros of the big q-Bessel functions. In particular, we prove new orthogonality relations for functions which are similar to the one for the classical Bessel functions. Also we give some applications related to the sampling theory.